Sex Modifies the Association of Fibroblast Growth Factor 21 With Subclinical Carotid Atherosclerosis - Chee, Yingjie; Toh, Grace Lx; Lim, Chien Joo; Goh, Liuh Ling; Dalan, Rinkoo (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Fibroblast growth factor 21 (FGF21), an emerging metabolic hepatokine, is associated with atherosclerosis. An interaction with sex has been described in various populations. We aimed to study whether sex modulates the relationship between FGF21 and subclinical carotid atherosclerosis in a diabetes enriched multi-ethnic population of Singapore. We explore differences in intermediary mechanisms, in terms of hypertension, lipids and inflammation, between FGF21 and atherosclerosis. Methods: We recruited 425 individuals from a single diabetes centre in Singapore and demographics, anthropometry, metabolic profile, FGF21 and carotid ultrasonography was performed. Multivariable logistic regression models was used to study the association between subclinical atherosclerosis and FGF21 adjusting for age, ethnicity, BMI, HbA1c, systolic and diastolic blood pressure and LDL-cholesterol separately for males and females as 2 groups after an interaction test. Results: An interaction test assessing interaction by sex on the relationship between subclinical atherosclerosis and FGF21 showed significant interaction with sex (Pinteraction=0.033). In the female subgroup, significant independent associations of standardized lnFGF-21 with subclinical atherosclerosis was seen, with 1SD increment in lnFGF-21 being associated with 1.48-fold (95%CI: 1.03, 2.12), p=0.036) increase in risk. In the male subgroup, the association of subclinical atherosclerosis with standardised lnFGF21 was not significant (OR (95%CI): 0.90 (0.63, 1.28); p=0.553). We found sex interactions with pulse pressure being significantly associated in females only and triglycerides and C-reactive protein being associated with males only. Conclusion: FGF21 is positively associated with subclinical carotid atherosclerosis in women, but not in men. The sex-racial patterns in the mechanisms by which FGF21 causes subclinical atherosclerosis needs to be explored in larger population based studies and mechanistically studied in greater details.